Carbon fiber reinforced vs titanium implants for fixation in spinal metastases: A comparative clinical study about safety and effectiveness of the new "carbon-strategy". (May 2020) - Cofano, Fabio; Di Perna, Giuseppe; Monticelli, Matteo; Marengo, Nicola; Ajello, Marco; Mammi, Marco; Vercelli, Giovanni; Petrone, Salvatore; Tartara, Fulvio; Zenga, Francesco; Lanotte, Michele; Garbossa, Diego
Highlights: Carbon fiber reinforced (CFR)-PEEK implants have been developed for spinal fixation in oncological disease. CFR-PEEK implants constitute a feasible and effective way to restore stability as standard titanium. Further studies are needed to clarify their potentially enormous oncological advantagess. Abstract: In spinal oncology traditional titanium implants could significantly impair evaluation of postoperative imaging because of artifacts, potentially affecting proper planning and execution of radiotherapy and adequate radiological follow-up to rule out progression of the disease. This is why carbon fiber reinforced (CFR)-PEEK implants have been developed for spinal fixation. The advantages of this system include fewer artifacts on imaging, potentially improving the execution and quality of radiotherapy, with also a reduced scattering effect to neighboring tissues. A comparative clinical and radiological study between new CFR-PEEK and standard titanium implants is described. Data recorded for each case included patient demographics, clinical, radiological and surgical data, intra- and postoperative complications, follow-up information. The goal of this study was to verify the safety and effectiveness of CFR-PEEK devices compared to standard titanium implants. A total number of 78 patients were reviewed. 36 patients underwent CFR-PEEK fixation, while titanium implants were used for 42 patients. Functional recovery was obtained in both groups and registered at last follow-up in terms of axial pain and neurological status. No significative differences were found between the two groups in terms of post-operative clinical complications and hardware-related complications. CFR-PEEK implants constitute a feasible and effective way to restore stability in metastatic spine tumors. This study found a non inferior favorable profile in terms of intraoperative and postoperative complications and functional recovery, compared to titanium. Further prospective studies are needed to clarify the potential oncological advantage of their radiolucency.